Burkholderia phytofirmans PsJN induces long-term metabolic and transcriptional changes involved in Arabidopsis thaliana salt tolerance - Pinedo, Ignacio; Ledger, Thomas; Greve, Macarena; Poupin, María J. (Frontiers in Plant Science, 2015)
Salinity is one of the major limitations for food production worldwide. Improvement of plant salt-stress tolerance using Plant-Growth Promoting rhizobacteria (PGPR) has arisen as a promising strategy to help overcome this limitation. However, the molecular and biochemical mechanisms controlling PGPR/plant interactions under salt-stress remain unclear. The main objective of this study was to obtain new insights into the mechanisms underlying salt-stress tolerance enhancement in the salt-sensitive Arabidopsis thaliana Col-0 plants, when inoculated with the well-known PGPR strain Burkholderia phytofirmans PsJN. To tackle this, different life history traits, together with the spatiotemporal accumulation patterns for key metabolites and salt-stress related transcripts, were analyzed in inoculated plants under short and long-term salt-stress. Inoculated plants displayed faster recovery and increased tolerance after sustained salt-stress. PsJN treatment accelerated the accumulation of proline and transcription of genes related to ABA signaling (RD29A and RD29B), ROS scavenging (APX2) and detoxification (GLYI7), and down-regulated the expression of LOX2 (related to JA biosynthesis). Among the general transcriptional effects of this bacterium, the expression pattern of important ion-homeostasis related genes was altered after short and long-term stress (AKT1, HKT1, NHX2 and SOS1). In all, the faster and stronger molecular changes induced by the inoculation suggest a PsJN-priming effect, which may explain the observed tolerance after short-term and sustained salt-stress in plants. This study provides novel information about possible mechanisms involved in salt-stress tolerance induced by PGPR in plants, showing that certain changes are maintained over time. This opens up new venues to study these relevant biological associations, as well as new approaches to a better understanding of the spatiotemporal mechanisms involved in stress tolerance in plants.